2019
DOI: 10.1177/1550147719833629
|View full text |Cite
|
Sign up to set email alerts
|

Individual cylinder air–fuel ratio estimation and control for a large-bore gas fuel engine

Abstract: For internal combustion engines with multi-cylinders, the differences of fuel injection, air distribution, and even exhaust gas recirculation between cylinders may result in cylinder-to-cylinder imbalance, and then the exhaust emission and engine performance will be poor. The individual cylinder air-fuel ratio control is one of the important techniques used to improve fuel economy and reduce exhaust emission. For the large-bore gas fuel engine with gas fuel injection devices, their mass flow rates would be aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Wang et al 2 proposed an individual cylinder air-fuel ratio estimation algorithm for a gas fuel engine with asymmetrical exhaust runners. The proposed algorithm is based on Kalman filtering where the coefficient matrix update step is added to the iterative process of common Kalman observer.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 2 proposed an individual cylinder air-fuel ratio estimation algorithm for a gas fuel engine with asymmetrical exhaust runners. The proposed algorithm is based on Kalman filtering where the coefficient matrix update step is added to the iterative process of common Kalman observer.…”
Section: Discussionmentioning
confidence: 99%
“…Universal Exhaust Gas Oxygen (UEGO) sensors placed at the exhaust can provide an air-fuel ratio estimate. Although usually limited to an average engine AFR every cycle (Franceschi et al, 2007;Ebrahimi et al, 2012), some studies aimed to quantify the contribution of each cylinder on the AFR measured by a single UEGO sensor by modeling the exhaust phenomena and dynamics (Chauvin et al, 2006;Suzuki et al, 2007;Cavina et al, 2010;Wang et al, 2019;Guardiola et al, 2019c). In-cylinder pressure can also be used to estimate the composition of the mixture in the cylinder: in Tunestål and Hedrick (2003); Di Leo (2015); Finesso and Spessa (2015), the authors determine the AFR by an inverse combustion model and in-cylinder pressure reading, while in Guardiola et al (2014); Broatch et al (2015) investigations suggested to use the resonant frequency of the in-cylinder pressure oscillations to estimate the overall trapped mass.…”
Section: Introductionmentioning
confidence: 99%